Hospitalizations in Dialysis Patients in Canada: A National Cohort Study. Issue 1 (1st June 2018) - Molnar, Amber O.; Moist, Louise; Klarenbach, Scott; Lafrance, Jean-Philippe; Kim, S. Joseph; Tennankore, Karthik; Perl, Jeffrey; Kappel, Joanne; Terner, Michael; Gill, Jagbir; Sood, Manish M.
Background: Hospitalizations of chronic dialysis patients have not been previously studied at a national level in Canada. Understanding the scope and variables associated with hospitalizations will inform measures for improvement. Objective: To describe the risk of all-cause and infection-related hospitalizations in patients on dialysis. Design: Retrospective cohort study using health care administrative databases. Setting: Provinces and territories across Canada (excluding Manitoba and Quebec). Patients: Incident chronic dialysis patients with a dialysis start date between January 1, 2005, and March 31, 2014. Patients with a prior history of kidney transplantation were excluded. Measurements: Patient characteristics were recorded at baseline. Dialysis modality was treated as a time-varying covariate. The primary outcomes of interest were all-cause and dialysis-specific infection-related hospitalizations. Methods: Crude rates for all-cause hospitalization and infection-related hospitalization were determined per patient year (PPY) at 7 and 30 days, and at 3, 6, and 12 months postdialysis initiation. A stratified, gamma-distributed frailty model was used to assess repeat hospital admissions and to determine the inter-recurrence dependence of hospitalizations within individuals, as well as the hazard ratio (HR) attributed to each covariate of interest. Results: A total of 38 369 incident chronic dialysis patients were included: 38 088 adults and 281 pediatric patients (age less than 18 years). There were 112 374 hospitalizations, of which 11.5% were infection-related hospitalizations. The all-cause hospitalization rate was similar for all adult age groups (age 65 years and older: 1.40, 1.35, and 1.18 admissions PPY at 7 days, 30 days, and 6 months, respectively). The all-cause hospitalization rate was higher for pediatric patients (1.67, 2.48, and 2.47 admissions PPY at 7 days, 30 days, and 6 months, respectively; adjusted HR: 2.73, 95% confidence interval [CI]: 2.37-3.15, referent age group: 45-64 years). Within the first 7 days after dialysis initiation, patients on peritoneal dialysis had a higher risk of all-cause hospitalization (HR: 1.27, 95% CI: 1.07-1.50) and infection-related hospitalization (HR: 2.05, 95% CI: 1.19-3.55) compared with patients on hemodialysis. Beyond 7 days, the risk did not differ significantly by dialysis modality. Female sex and Indigenous race were significant risk factors for all-cause hospitalization. Limitations: The cohort had too few home hemodialysis patients to examine this subgroup. The outcome of infection-related hospitalization was determined using diagnostic codes. Dialysis patients from Manitoba and Quebec were not included. Conclusions: In Canada, the rates of hospitalization were not influenced by dialysis modality beyond the initial 7-day period following dialysis initiation; however, the rate of hospitalization in pediatric patients was higher than in adults at every time frame examined.